Implementation of the updated 2015 Commission for Hospital Hygiene and Infection Prevention (KRINKO) recommendations "Prevention and control of catheter-associated urinary tract infections" in the hospitals in Frankfurt/Main, Germany - Heudorf, Ursel; Grünewald, Miriam; Otto, Ulla (German Medical Science GMS Publishing House, 2016)
Aim: The Commission for Hospital Hygiene and Infection Prevention (KRINKO) updated the recommendations for the prevention of catheter-associated urinary tract infections in 2015. This article will describe the implementation of these recommendations in Frankfurt's hospitals in autumn, 2015.Material and methods: In two non-ICU wards of each of Frankfurt's , inspections were performed using a checklist based on the new KRINKO recommendations. In one large hospital, a total of were inspected. The inspections covered the structure and process quality (operating instructions, training, indication, the placement and maintenance of catheters) and the demonstration of the preparation for insertion of a catheter using an empty bed and an imaginary patient, or insertion in a model.Results: Operating instructions were available in all hospital wards; approximately half of the wards regularly performed training sessions. The indications were largely in line with the recommendations of the KRINKO. Alternatives to urinary tract catheters were available and were used more often than the urinary tract catheters themselves (15.9% vs. 13.5%). In accordance with the recommendations, catheters were placed without antibiotic prophylaxis or the instillation of antiseptic or antimicrobial substances or catheter flushing solutions. The demonstration of catheter placement was conscientiously performed. Need for improvement was seen in the daily documentation and the regular verification of continuing indication for a urinary catheter, as well as the omission of regular catheter change.Conclusion: Overall, the recommendations of the KRINKO on the prevention of catheter-associated urinary tract infections were adequately implemented. However, it cannot be ruled out that in situations with time pressure and staff shortage, the handling of urinary tract catheters may be of lower quality than that observed during the inspections, when catheter insertion was done by two nurses. Against this background, a sufficient number of qualified staff and regular ward rounds by the hygiene staff appear recommendable.